PENGARUH PENERAPAN SISTEM INFORMASI KEUANGAN DAERAH, PENERAPAN STANDAR AKUNTANSI PEMERINTAH DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS INFORMASI PELAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Pada SKPD Kabupaten Kuantan Singingi) - Putri, Audiana; ', Desmiyawati; ', Al Azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research aims to analyze of influencing implementing financial information system, implementing accounting government standard and utilization of information technology to the quality of information financial reporting. Object of this research is department of SKPD Kuantan Singingi. There are eighty one questionnaires were sent, and eighty one questionnaires are returned. That data are analyzed by linear regression method and SPSS program version 19. The variables were examined implementing financial information system, implementing accounting government standard and utilization of information technology to the quality of information financial reporting. The results of this research showed implementing financial information system has an effect to the quality of information financial reporting with 0,001 significance, implementing accounting government standard has an effect to the quality of information financial reporting with 0,003 significance and utilization of information technology has an effect to the quality of information financial reporting with 0,001 significance. The results of this research also showed that coefficient R square is 75,8%. Each independent variables, gives the strong influence to dependent variable, it means independents variables could explain dependent variable well.. All variables also have strong relation with variable dependents in this research.Keywords: information, financial, accounting, government and quality